IMPACT DES DEPENSES PUBLIQUES D’EDUCATION SUR LACROISSANCE ECONOMIQUE EN CÔTE D’IVOIRE - Coulibaly Mamadou (European Scientific Journal, ESJ, 2013)
Does Education stimulate economic growth? An affirmative answer to this question is not as obvious as one might think fisrt. That is why this study uses the time series analysis to examine the true functional relationship between public education spending and economic growth in Côte d'Ivoire during the period 1970-2005The estimation results show that these expenditures have a significantly positive impact on economic growth. In the short term, the estimated error-correction model shows that increases of 1% of the growth rate of gross fixed capital formation and education spending lead increases of 0.1659% and 5.795% of the rate of economic growth. Education spending thus appears as the second driving force of economic growth process